(untitled) (Research, Society and Development, 2020)
This work aims to describe the necessary recommendations in the care of patients in dental clinics in the midst of the Covid-19 pandemic. Based on that, a literature review was carried out with a systematic search for articles in the Medical Publications (PubMed), Scientific Electronic Library Online (SciELO) and CAPES / MEC Portal of Journals, using the keywords “Covid-19 (Covid- 19)” and “Dentistry (Dentistry)”, with the Boolean operator “And”. Four articles and six official documents on Covid-19 integrated this review. In view of the already recommended biosafety indications, such as hand hygiene and the use of personal protective equipment (PPE), the use of the N95 or PFF2 mask and facial visors is added. Another requested measure is to perform a screening, before dental care, in search of possible information that indicates a possible contamination by the virus. In view of the above, in a period of epidemic outbreak, the adoption of stricter biosafety practices is necessary, as well as recommending urgent / emergency care.